2019
DOI: 10.1016/j.joca.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic value of a type X collagen neo-epitope biomarker for knee osteoarthritis

Abstract: s u m m a r yObjective: Phenotypic changes of chondrocytes toward hypertrophy might be fundamental in the pathogenesis of osteoarthritis (OA), of which type X collagen (Col10) is a well-known marker. The purpose was to develop a specific immunoassay for blood quantification of a newly identified neo-epitope of type Col10 to assess its diagnostic value for radiographic knee OA. Methods: A neo-epitope of Col10 was identified in urine samples from OA patients. A monoclonal antibody against the neo-epitope was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 38 publications
1
27
1
Order By: Relevance
“…It is highly expressed by hypertrophic chondrocytes as a marker of hypertrophic regeneration. In sections of human osteoarthritic cartilage, Col10 was found around hypertrophic chondrocyte clusters in the deep zone close to tidemark ( He et al., 2019 ). Besides the collagens, aggrecan, known as a cartilage-specific proteoglycan core protein, is another crucial component of cartilage ECM ( Hu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly expressed by hypertrophic chondrocytes as a marker of hypertrophic regeneration. In sections of human osteoarthritic cartilage, Col10 was found around hypertrophic chondrocyte clusters in the deep zone close to tidemark ( He et al., 2019 ). Besides the collagens, aggrecan, known as a cartilage-specific proteoglycan core protein, is another crucial component of cartilage ECM ( Hu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutant or abnormal human COL10A1 expression are often accompanied by abnormal chondrocyte hypertrophy, as seen in children and young adults with multiple skeletal dysplasia (Warman et al, 1993;Ikegawa et al, 1998;Bateman et al, 2005;Lu et al, 2014;Ain et al, 2018). Abnormal COL10A1 expression and chondrocyte hypertrophy are also observed in elderly individuals with osteoarthritis (OA), who show osteophyte formation involving a process mimicking the endochondral pathway (von der Mark et al, 1995;Girkontaite et al, 1996;Drissi et al, 2005;Lamas et al, 2010;Saito et al, 2010;Armiento et al, 2019;Gratal et al, 2019;He et al, 2019). Recent studies show that intact trimeric noncolla-genous 1 domain of type X collagen is a degradation by-product of endochondral ossification released into the circulation in proportion to the overall growth plate.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, microarray studies of BML tissue isolates have shown increased expression of proteases, osteogenic and chondrogenic molecules such as matrix metalloproteinase (MMP) 13 and molecules associated with Wnt signaling, suggestive of local repair processes and heavy remodeling [75]. OA development is associated with changes in chondrocyte behavior, including matrix calcification and expression of hypertrophic markers such as MMP13 and type X collagen, which are both signs of hypertrophy [76,77]. These phenomena, in many cases, appear similar to the function of hypertrophic chondrocytes in the growth plate of long bones undergoing endochondral ossification during growth.…”
Section: Fibrodysplasia Ossificans Progressivathe Systemic Ossificatimentioning
confidence: 83%
“…The marker was also associated with increased severity defined by KL grade. Interestingly the level of Col10neo was higher in OA patients compared to RA patients suggesting that type X collagen expression and chondrocyte hypertrophy not surprisingly is more pronounced in OA compared to RA [76,107]. Although not a neo-epitope, the cartilage residing cartilage oligomeric protein (COMP) is increased in serum and synovial fluid of OA patients [102,103], and one study has shown that high baseline levels predict development of radiograph knee OA [104].…”
Section: Tissue Turnover Markers In Osteoarthritismentioning
confidence: 99%